Study of the exclusive ed-skattering at VEPP-3; Particles and nuclei - Osipov A. V.; Sidorov A. A.; Stibunov V. N. Victor Nikolaevich; Nikolenko D. M.; Popov S. G.; Rachek A. A.; Toporkov D. K.; Tsentalovich E. L.; Wojtsekhowski B. B. (1997, 1997)
В фонде НТБ ТПУ отсутствует